Specific antibody responses to the variable surface glycoproteins of Trypanosoma congolense in infected cattle - Masake, R.A.; Musoke, J.; Nantulya, V.M. (Wiley, 1983)
Summary Sera from cattle infected with three Trypanosoma congolense clones (ILNat 2.1, ILNat 3.1 and ILRAD 588) derived from different stocks were analysed for the presence of specific antibodies against the surface glycoproteins (VSGs) of the infecting trypanosomes using the solid and liquid‐phase radioimmunoassays and the neutralization of infectivity test. High levels of IgM, IgGi and IgG2 antibodies against the VSGs of the infecting variable antigen types (VATs) as well as other VATs that arose during the course of infection were detected. In addition, 11 out of 12 infected animals showed recurrent peaks of antibody activity against the infecting trypanosomes. The recurrent peaks of antibody activity against the VSGs of the infecting organisms would suggest either a reappearance of trypanosomes of the infecting types or emergence of organisms that bear similar surface determinants. In contrast to the studies on murine trypanosomiasis, there was little or no antibody activity against 2, 4, 6‐trinitrophenylated bovine serum albumin (TNP‐BSA) in sera from these cattle.